The Institutional Restructuring of the Chinese Communist Party under Xi Jinping - Rifqillah, Muhammad Nail (Hasanuddin Journal of International Affairs, 2025)
This paper investigates the internal restructuring of the Chinese Communist Party (CCP) under Xi Jinping’s leadership and its influence on policy-making and foreign policy behavior. Drawing on an integrated theoretical framework that combines the Bureaucratic Politics Model and Two-Level Game Theory, the study examines how China's increasingly centralized political architecture allows for a more coherent implementation of policies from the top down. The paper argues that the restructuring of the CCP through the consolidation of decision-making power within the Politburo Standing Committee, the elevation of Party-led commissions, and the expanding control over state bureaucracies not only enhance administrative efficiency but also to strategically align domestic priorities with China’s international ambitions. Domestic economic policies, often managed by Party-led bureaucracies, now function as instruments of external leverage. This analysis contributes to a more nuanced understanding of China's domestic–international policy nexus, particularly how centralized authority and controlled bureaucratic channels reduce fragmentation in domestic preferences, thereby shaping China’s negotiation behavior, strategic signaling, and foreign policy consistency.